Anetta Bogusława Strawińska, Leksyka północnokresowa jako element deskrypcji zagadnień ortoepicznych w poradnikach Aleksandra Walickiego i Aleksandra Łętowskiego, Wydawnictwo PRYMAT, Seria: Białostockie Studia Językoznawcze (tom 18), Białystok 2022, ss. 192, ISBN 978-83-7657-465-3 - Davlevič, Miroslav (Slavistica Vilnensis, 2023)
The publication of Anetta Boguslava Stravinska Leksyka północnokresowa jako element deskrypcji zagadnień ortoepicznych w poradnikach Aleksandra Walickiego i Aleksandra Łętowskiego (2022) belongs both to a number of studies of the Polish language in Lithuania, and to studies of the correctness of Polish speech. The purpose of the study is to compare examples from manuals on correct speech by Alexander Valitsky and Alexander Lentovsky, to establish the linguistic consciousness of both Polish speakers at the end of the 19th and early 20th centuries, and the authors of the manuals. The book under review is an interesting and valuable contribution, complementing previous studies of the Polish language in the Kres. The monograph will also provide scientific and didactic assistance in further studying the problems of the culture of Polish speech in Lithuania.